Eksplorasi Unsur Matematika pada Batu Kubur Bersejarah di Kampung Bukaregha - Carmela Ule, Christofoura; Dawa, Marlince; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore and identify mathematical elements found in the historical stone graves located in Bukaregha Village, Loura District, Southwest Sumba Regency. These stone graves are cultural heritage artifacts of the Sumbanese people, possessing significant historical, philosophical, and geometric values. This research uses a descriptive qualitative method with an ethnomathematical approach, focusing on the relationship between local culture and mathematical concepts. Data were collected through field observations, interviews with traditional leaders, and documentation of the stone grave structures. The findings reveal that the structure of the stone graves contains various mathematical elements, such as geometric shapes (squares, rectangles, blocks, and cubes) as well as concepts of length and volume measurement. These results indicate that the Sumbanese community has intuitively applied mathematical principles within their cultural practices and traditional architectural designs. This study is expected to serve as a reference for the development of ethnomathematics-based learning, particularly in integrating mathematics with local wisdom to enhance relevance and meaningful learning for students.